2005
DOI: 10.1111/j.1479-828x.2005.00419.x
|View full text |Cite
|
Sign up to set email alerts
|

Introduction of early medical abortion in New Zealand: An audit of the first 67 cases

Abstract: EMTOP with mifepristone and misoprostol was successfully introduced and the experience provides useful data for others contemplating a similar service.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…22 This paper presents our experience with a second trimester induction of labour regimen based on that developed in Aberdeen. 23 The data published on this protocol to date have primarily come from Scotland, 1,13,14,22,23 with one paper from the USA. 25 This paper will describe the first use of this regimen in Australasia.…”
Section: Introductionmentioning
confidence: 99%
“…22 This paper presents our experience with a second trimester induction of labour regimen based on that developed in Aberdeen. 23 The data published on this protocol to date have primarily come from Scotland, 1,13,14,22,23 with one paper from the USA. 25 This paper will describe the first use of this regimen in Australasia.…”
Section: Introductionmentioning
confidence: 99%
“…An audit was conducted of the first 67 patients undergoing MTOP in New Zealand between 24 April 2002 and 31 May 2003 at level J 12 . This study found that women choosing MTOP were significantly older than surgical patients, differed by ethnicity and were less likely to have had a previous TOP, whereas patients presenting to AMAC showed no significant difference on these characteristics.…”
Section: Discussionmentioning
confidence: 96%
“…Similarly, nulliparous women were more likely to choose MTOP than multiparous women, whereas level J found no difference in parity between MTOP and STOP patients. It should be noted, however, that level J results do not report the parity of 548 (17.9%) of their STOP patients 12 . It might be expected that women who have never had a baby nor a miscarriage would be more likely to chose MTOP rather than a surgical procedure.…”
Section: Discussionmentioning
confidence: 97%